Membandingkan Perbedaan Gelombang Bunyi Menggunakan Benda-Benda Sederhana - Nurmalasari, Dewi; Azzahra, Siti Fatihah; N, Nurmayanti (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to compare the differences in sound waves produced by simple objects commonly found in the surroundings. The research method used is a descriptive qualitative approach. Data collection was carried out through direct experiments using simple objects such as a tin can telephone, used milk cans, and wine glasses. These objects functioned as tools or visual aids. The results of the experiments were then described in the form of a report, accompanied by supporting literature reviews. The results of the experiments suggest that sound is produced due to the presence of air and vibrations. A tin can telephone with a shorter string produced clearer sound. This is due to the faster wave propagation through the string. Mediums that contain empty space tend to produce louder and sharper sounds, as there are fewer objects to obstruct or absorb the sound. For instance, when one side of an open can is struck with a spoon, it produces a very loud sound. Similarly, experiments using wine glasses filled with varying amounts of water showed that the amount of water affects the sound produced. Variations in string length on the tin can telephone, the way the cans are positioned, and the amount of water in the glasses all influence the type of sound that is generated.